Carbon dioxide photo/electroreduction with cobalt. Issue 28 (2nd July 2019) - Li, Caihong; Tong, Xin; Yu, Peng; Du, Wen; Wu, Jiang; Rao, Heng; Wang, Zhiming M.
Abstract : This review summarizes the recent progress made in using cobalt-based catalysts for photo/electrocatalytic CO2 reduction. Abstract : The unrestrained consumption of fossil fuels increases the concentration of carbon dioxide (CO2 ) in the atmosphere and has exacerbated the worldwide energy crisis and global warming. CO2 catalytic reduction to carbonaceous value-added fuel molecules and chemical feedstocks can release our dependence on fossil fuels together with CO2 mitigation. This review focuses on recent advances in CO2 photo/electroreduction based on cost-effective and earth-abundant cobalt catalysts. It consists of catalytic mechanisms, material preparation and characterization and catalytic performance optimization. There are five aspects used to evaluate the catalytic performances of catalysts for CO2 photo/electroreduction, including CO2 adsorption, activation, conversion, product selectivity and catalyst stability. To enhance the catalytic selectivity or activity, several strategies, such as modification, incorporation of dopants, varying synthetic methods, reaction solutions, etc. are discussed. This review summarizes the recent progress made in CO2 photo/electroreduction with Co catalysts and serves as an up-to-date reference for designing more efficient and stable Co catalysts for CO2 reduction.